Multiparametric diffusion-weighted MRI for renal microstructural assessment in patients with primary aldosteronism at varying direct renin concentrations. - Wen, Deying; Liang, Ailin; Du, Qinglin; Li, Wen; Zhao, Ling; Qiu, Yue; Wang, Tengxin; Li, Zheng; Liang, Huilou; Zhang, Bo; Ren, Yan; Sun, Jiayu (Abdominal Radiology, 2026)
Purpose: To utilize multiparametric diffusion-weighted imaging (DWI) to detect and quantify renal microstructural alterations in patients with primary aldosteronism (PA) at varying direct renin concentrations (DRC), and to explore the correlations between DWI-derived biomarkers and renal function biochemical indices. Materials and methods: This study included 50 patients and 32 healthy controls (HCs). Participants underwent 3.0 T MRI using monoexponential, intravoxel incoherent motion, and stretched-exponential DWI models. Two observers independently analyzed diffusion parameters, including apparent diffusion coefficient (ADC), fraction of fast diffusion (f), slow diffusion coefficient (Ds), fast diffusion coefficient (Df), distributed diffusion coefficient (DDC), and anomalous exponent (α). Group comparisons were conducted using t-tests, Mann–Whitney U tests, or ANOVA; receiver operating characteristic (ROC) curve analysis was used. Correlations between diffusion parameters and renal function biomarkers were analyzed using Pearson or Spearman correlation tests. Results: Compared to HCs, PA patients with abnormal DRC exhibited significantly lower cortical and medullary ADC, f, and DDC values and higher cortical α. ROC analysis demonstrated that combining these parameters achieved an AUC of 0.884 with 90.0% sensitivity and 81.5% specificity for distinguishing DRC-abnormal patients from HCs. Medullary f was reduced in the abnormal DRC group versus normal DRC group. The ROC analysis for distinguishing these two groups yielded an AUC of 0.790, with a sensitivity of 85.30% and a specificity of 62.50%. Correlations showed an inverse relationship between medullary Ds and creatinine, a positive correlation between medullary f and uric acid, and a negative correlation of cortical DDC with creatinine and cystatin C. Conclusion: Multiparametric DWI enables precise detection and quantification of renal microstructural abnormalities in PA patients. Patients with abnormal DRC exhibit more pronounced renal microstructural alterations compared to DRC-normal group. Notably, observed correlations between specific diffusion metrics and renal function biomarkers underscore their potential clinical applicability for non-invasive monitoring of PA-associated renal injury.